DESENVOLVIMENTO DE DIABETES MELITTUS APÓS TRANSPLANTE RENAL - RELATO DE CASO - Bruna Maria Bianchi das Neves; Ana Paula Nunes; Aryane Martins Amorim; Lucas Kenji Sakai; Luis Eduardo Bersani Amado (Editora Uningá, 2019)
Diabetes Mellitus is a well-known complication of immunosuppressive therapy that causes an increase in cardiovascular morbidity and mortality and a decrease in graft survival. This condition was initially recognized in recipients of renal transplantation by Starzl in 1964, and has since been cited. The report shows the opening of the disease in a recently transplanted patient with a classic case of diabetic ketoacidosis - a situation rarely described in the literature due to its rarity.